A new species of Holophloeus Jordan (Coleoptera: Anthribidae) from eastern Madagascar with ecological notes on it and H. tuberosus (Fairmaire, 1897) - Trýzna, Miloš; Baňař, Petr (Zootaxa, 2020)
A new species, Holophloeus loebli Trýzna & Baňař sp. nov. (Anthribidae: Anthribinae: Discotenini), from east Madagascar is described. Male genitalia are studied and illustrated, and color photographs are provided. A comparison is provided with the other known Madagascan species of the genus, H. tuberosus (Fairmaire, 1897). Ecological notes, including color photographs of habitats, on H. loebli and H. tuberosus are provided.